A Comparative Study of Employee Engagement in the Public and Private Sector Oil Companies in India - Praveen Kumar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
The oil boom in the country has reduced India’s reliance on agriculture and redirected it to the oil and petroleum sector. The public sector is a key component of the Indian economy, but due to the country’s growing population, the private sector must also expand. The current research study contrasts employee involvement in public and private Indian oil sector enterprises. It seeks to pinpoint the variations in how employee engagement is understood. Additionally, this study compares the cognitive, emotional, and behavioral levels of employee involvement in the aforementioned areas. A systematic questionnaire was used to gather primary data from 155 respondents, who provided information about themselves. Out of those, 85 respondents worked for public and 70 for private oil and gas enterprises. The data were gathered using the snowball sampling technique. Middle-level employees are the study’s target response population. The findings showed that while there is no significant difference in employee involvement on a behavioral level between public and private enterprises in the oil and petroleum sector, there are some significant variations on a cognitive and emotional level.